FIXTURING DEVICE FOR DRILLING A STRAIGHT SHAFT - Florin Susac; Valentin Tabacaru; Georgiana-Alexandra Costin (Journal of Industrial Design and Engineering Graphics, 2017)
The paper presents a fixturing device used for machining by drilling a straight shaft. The shaft was manufactured on EMCO CONCEPT TURN 55 CNC. The blank used was a bar with circular crosssection. The orientation and fixing scheme of the part and the orientation elements for fixturing device are presented as they were drawn in Autodesk Inventor and AutoCAD software.